Pathogenic Mechanisms Associated With Different Clinical Courses of Multiple Sclerosis - Lassmann, Hans (Frontiers in Immunology, 2019)
In the majority of patients multiple sclerosis starts with a relapsing remitting disease (RRMS), which may at later times transform into secondary progressive disease (SPMS). In a minority of patients the relapsing remitting disease is skipped and the patients show progression from the onset (primary progressive MS, PPMS). Evidence obtained so far indicate major differences between RRMS and progressive MS, but no essential differences between SPMS and PPMS, with the exception of a lower incidence in the global load of focal white matter lesions and in particular in the presence of classical active plaques. We suggest that in MS patients two types of inflammation occur, which develop in parallel but partially independent from each other. The first is the focal bulk invasion of T- and B-lymphocytes with profound blood brain barrier leakage, which predominately affects the white matter and which gives rise to classical active demyelinated plaques. The other type of inflammation is a slow accumulation of T-cells and B-cells in the absence of major blood brain barrier damage in the connective tissue spaces of the brain, such as the meninges and the large perivascular Virchow Robin spaces, where they may form aggregates or in most severe cases structures in part resembling tertiary lymph follicles. This type of inflammation is associated with the formation of subpial demyelinated lesions in the cerebral and cerebellar cortex, with slow expansion of pre-existing lesions in the white matter and with diffuse neurodegeneration in the normal appearing white or grey matter. The first type of inflammation dominates in acute and relapsing MS. The second type of inflammation is already present in early stages of MS, but gradually increases with disease duration and patient age. CD8+ T-lymphocytes remain in the brain and spinal cord as tissue resident cells, which focally propagate neuroinflammation, when they re-encounter their cognate antigen. B-lymphocytes appear to propagate demyelination and neurodegeneration, most likely by producing soluble neurotoxic factors. Key open questions in MS research are the identification of the target antigen recognized by tissue resident CD8+ T-cells and B-cells and the molecular nature of the soluble inflammatory mediators, which trigger tissue damage.